Granulomatous myelitis associated with hemorrhagic syndrome due to consumption of Vicia villosa by cattle - Sonne, Luciana (2010)
An unusual case of spontaneous Vicia villosa poisoning affected a 6-year-old Holstein cow. Although the most striking findings included a generalized hemorrhagic condition associated with granulomatous myelitis, histological lesions typically seen with the vetch-associated systemic granulomatous syndrome were also present. Prominent gross findings were bloody nasal and oral discharges, disseminated hemorrhages, and bloody feces. Generalized hemorrhages associated with infiltration of numerous organs by lymphocytes, plasma cells, macrophages, multinucleated giants cells, and eosinophils were the main microscopic findings. Anti-CD68 immunostaining confirmed the presence of moderate histiocytic infiltrate and multinucleated giant cells in the bone marrow. These changes in the bone marrow probably caused the generalized hemorrhagic changes described here. __________________________________________________________________________________________ ABSTRACT